Manajemen Pelayanan Sekolah Minggu di Gereja Kalimantan Evangelis Jemaat Kasih Marawan Lama - Margaret Wela Victoria; Rinto Hasiholan Hutapea (Institut Agama Kristen Negeri Palangka Raya, 2022)
This article aims to analyze the management of Sunday Schools in the Kalimantan Evangelical Church of Kasih Marawan Lama, South Barito Regency, Central Kalimantan Province. The problem is that the church is not aware that Sunday schools are experiencing some management-related problems. This caused the Sunday school categorical worship service to be unable to perform its functions properly. This research uses a qualitative method by examining phenomena that occur in the field and providing an explanation of what the author sees and feels and describes the results of interviews with informants. The results of the study revealed that the work program was prepared by Sunday School teachers, then the panel evaluated and reviewed each work program design that had been planned. Sunday School financial management of income and expenses is reported on a quarterly basis. The chairman of the assembly and the Sunday School teacher worked together to solve the Sunday School problem. The implementation of Sunday School services has not been running optimally and effectively. This has an impact on decreasing children's interest in coming to Sunday School services. The timing of the implementation of worship is also not appropriate and prevents children from coming. Evaluation of the performance of Sunday School teachers needs to be carried out to see the results of the implementation of Sunday School activities. Artikel ini bertujuan untuk menganalisis manajemen Sekolah Minggu di Gereja Kalimantan Evangelis Kasih Marawan Lama, Kabupaten Barito Selatan, Provinsi Kalimantan Tengah. Permasalahan gereja kurang menyadari bahwa sekolah minggu mengalami beberapa masalah terkait manajemen. Hal ini menyebabkan pelayanan ibadah kategorial sekolah minggu tidak dapat menjalankan fungsinya dengan baik. Penelitian ini menggunakan metode kualitatif dengan meneliti fenomena-fenomena yang terjadi di lapangan serta memberikan penjelasan atas apa yang dilihat dan dirasakan oleh penulis dan mendeskripsikan hasil wawancara dengan informan. Hasil penelitian mengungkapkan bahwa program kerja disusun oleh guru Sekolah Minggu, kemudian majelis mengevaluasi dan meninjau kembali setiap rancangan program kerja yang sudah direncanakan. Manajemen keuangan Sekolah Minggu terkait pemasukan dan pengeluaran dilaporkan setiap kunjungan triwulan. Ketua majelis dan guru Sekolah Minggu bekerja sama untuk menyelesaikan permasalahan Sekolah Minggu. Pelaksanaan pelayanan Sekolah Minggu belum berjalan dengan maksimal dan efektif. Hal ini berdampak pada menurunnya minat anak untuk datang dalam ibadah Sekolah Minggu. Pengaturan waktu pelaksanaan ibadah juga tidak sesuai dan membuat anak tidak datang. Evaluasi kinerja guru Sekolah Minggu perlu dilakukan untuk melihat hasil dari pelaksanaan kegiatan Sekolah Minggu.